2010
DOI: 10.1063/1.3457942
|View full text |Cite
|
Sign up to set email alerts
|

Rotational state specific dissociation dynamics of D2O via the C̃ electronic state

Abstract: The rotational state resolved photodissociation dynamics of D(2)O via the C state has been investigated using the D-atom Rydberg "tagging" time-of-flight technique, with a tunable vacuum ultraviolet photolysis light source. The photodissociation action spectrum of the D(2)O C<--X (3p(z)<--1b(1)) band has been recorded. The linewidths of rotational transitions have been determined by the Lorentzian profile simulation. Product kinetic energy distributions and angular distributions for individual rotational lines… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 27 publications
1
11
0
Order By: Relevance
“…For example, Ashfold et al obtained the fully resolved photo‐fragment fluorescence spectrum and suggested two separate predissociation mechanisms, via one homogeneous, rotational state‐independent, and one heterogeneous, rotational state‐dependent pathway . Yang and coworkers reported time‐of‐flight (TOF) spectra for the C band, which shows a dramatic variation in the product state distributions and its stereodynamics for different resonant levels . The relative probabilities of these two pathways depend strongly on the rotational quantum number .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, Ashfold et al obtained the fully resolved photo‐fragment fluorescence spectrum and suggested two separate predissociation mechanisms, via one homogeneous, rotational state‐independent, and one heterogeneous, rotational state‐dependent pathway . Yang and coworkers reported time‐of‐flight (TOF) spectra for the C band, which shows a dramatic variation in the product state distributions and its stereodynamics for different resonant levels . The relative probabilities of these two pathways depend strongly on the rotational quantum number .…”
Section: Introductionmentioning
confidence: 99%
“…62,78,79 Yang and coworkers reported time-of-flight (TOF) spectra for the C band, which shows a dramatic variation in the product state distributions and its stereodynamics for different resonant levels. 81,84,85 The relative probabilities of these two pathways depend strongly on the rotational quantum number. 86,87 Dynamic calculations were performed on a new set of reduceddimensional PESs for the e X, e A, 1 A 2 , e B, and e C states and nonadiabatic transitions between those states.…”
Section: Introductionmentioning
confidence: 99%
“…These alternations are reminiscent of those observed in the OH(X) fragments arising in the 121.6 nm photolysis of H2O5 and, as in that case, can be attributed to dynamical interferences between dissociation pathways via the CIs between the B and X states, most of which effects could be attributed to mass changes. [35][36][37] Here, we reveal a much more dramatic isotope effect, caused by accidental resonance, which leads to different dissociation rates, different dissociation mechanisms, and different product energy disposals following excitation to a common excited state of H2O and D2O.…”
Section: Methodsmentioning
confidence: 81%
“…38 The experimental technique used in this work is similar to that employed in the H 2 O/D 2 OC state photodissociation experiment. 35,36 Briefly, the D 2 O molecular beam was generated by expanding a mixture of 3% D 2 O in Ar at a stagnation pressure of 600-900 Torr through a 0.5 mm diameter pulsed nozzle. The expansion went through a skimmer into main chamber.…”
Section: Methodsmentioning
confidence: 99%
“…Rovibrational distributions of the OH/OD(A 2 + ) radical products were obtained from the OH/OD(A 2 + → X 2 ) fluorescence. 35,36 The results revealed two rotational quantum number-dependent dissociation mechanisms that produce strikingly different OH/OD internal state distributions. These conclusions are consistent with the results of previous studies, [32][33][34] which also indicated that the relatively slow predissociation rate of theC state (on ps time scale) leads to resolvable rotational structure.…”
Section: Introductionmentioning
confidence: 96%